Game-Based Learning with Roblox for EFL or ESL Learners: A Systematic Literature Review - Tira Nur Fitria (International Journal of Computer and Information System (IJCIS), 2026)
This research reviews and synthesizes existing studies on the use of Roblo as a game-based learning platform for English as a Foreign Language (EFL) and English as a Second Language (ESL) learners. This examines how Roblox has been implemented in language learning contexts, what language skills and competencies it supports, and what pedagogical strategies are most commonly applied. This study reviewed and synthesized previous research across different educational contexts. The selected studies gatehered from 2022 to 2025 and examine Roblox’s applications in STEM education, English language learning, higher education, religious studies, and broader skill development. The reviewed studies show that Roblox is a game-based learning platform across diverse educational contexts. Research published between 2022 and 2025 highlights its applications in STEM education, English language learning, higher education, religious studies, and broader skill development. In STEM fields, Roblox has been shown to support engineering, science, mathematics, and financial education through immersive simulations that enhance conceptual understanding, problem-solving, and analytical skills. In language learning, both learners and teachers view Roblox positively for improving vocabulary, reading comprehension, teamwork, and cultural exchange, although grammar accuracy continues to pose challenges. Beyond academic learning, Roblox fosters creativity, collaboration, innovation, and 21st-century skills, while also raising concerns regarding safety, overuse, and accessibility. Its versatility is further reflected in studies on religious education, promotional media, and metaverse schools, demonstrating broad potential across disciplines. Recent research also emphasizes the role of artificial intelligence in Roblox, particularly in enhancing game development, personalization, and learner engagement. Taken together, these studies suggest that Roblox is an effective platform for interactive, gamified, and collaborative learning, though careful pedagogical, technological, and ethical considerations are needed for its optimal implementation.